PELAKSANAAN RESTITUSI OLEH JAKSA PENUNTUT UMUM BAGI ANAK YANG MENJADI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL (ANALISIS PUTUSAN PN. LUBUK PAKAM NO:312/PID.SUS-ANAK/2019/PN LP) - Hendrik Dolok Tambunan; Ahmad Fauzi (JURNAL DOKTRIN REVIEW, 2022)
The trial process before the Panel of Judges in examining cases of criminal acts of sexual violence, it seems that children as victims are presented before the court only as witnesses in the trial process, without considering the rights of children as victims who must obtain compensation (restitution), compensation and rehabilitation , so that the judicial process in fulfilling the rights of victims has not implemented effective protection of victims, especially in cases of sexual violence involving children as victims who suffer more psychologically from trauma. Efforts to protect the law and rights possessed by children who are victims of criminal acts are the right to obtain restitution. The legal basis for regulating the restitution of children as victims of criminal acts of sexual violence is contained in Law no. 35 of 2009 and PP No. 43 of 2017. The public prosecutor has the authority to prosecute the defendant. 43 of 2017, the public prosecutor informs the victim of the rights of the victim of a crime of sexual violence to obtain restitution, and the procedure for submitting it before and/or in the trial process. Third, the obstacle faced by the prosecutor in applying for restitution in the prosecutor's letter of demand is law enforcement factors, not all public prosecutors have experience in handling the provision of restitution to victims of criminal cases of sexual violence.